2022
DOI: 10.1108/ijchm-05-2021-0579
|View full text |Cite
|
Sign up to set email alerts
|

Do tourists’ responsible behaviors shape their local food consumption intentions? An examination via the theory of planned behavior

Abstract: Purpose The primary purpose of this study is to reveal how the local food consumption intentions of international tourists are influenced by core variables of the theory of planned behavior (TPB). The secondary purpose is to explore the moderating role of responsible tourist behavior in these relationships. Design/methodology/approach The present research was conducted on international tourists visiting Antalya, Turkey. The research data, collected from a total of 457 respondents, were tested and analyzed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 105 publications
1
13
0
10
Order By: Relevance
“…According to Dedeoğlu et al (2022), the TPB is a model that enables the incorporation of new and additional factors while also proving important in understanding individuals’ food consumption behaviours. This study extended the TPB by including health consciousness, perceived nutrition of cereals, hedonic eating values, utilitarian eating values (Babin et al , 1994; Dhar and Wertenbroch, 2000; Voss et al , 2003), actual consumption of cereal products, cereal products consumption satisfaction, continuance of cereal consumption (Terry and O'Leary, 1995; Nystrand and Olsen, 2020; Sadiq et al , 2021) and other traditional TPB constructs such as attitudes towards cereal consumption and willingness to pay for cereals (behavioural intention) to measure the continuance of cereal consumption among the Generation Z cohort.…”
Section: Underpinning Theoriesmentioning
confidence: 99%
“…According to Dedeoğlu et al (2022), the TPB is a model that enables the incorporation of new and additional factors while also proving important in understanding individuals’ food consumption behaviours. This study extended the TPB by including health consciousness, perceived nutrition of cereals, hedonic eating values, utilitarian eating values (Babin et al , 1994; Dhar and Wertenbroch, 2000; Voss et al , 2003), actual consumption of cereal products, cereal products consumption satisfaction, continuance of cereal consumption (Terry and O'Leary, 1995; Nystrand and Olsen, 2020; Sadiq et al , 2021) and other traditional TPB constructs such as attitudes towards cereal consumption and willingness to pay for cereals (behavioural intention) to measure the continuance of cereal consumption among the Generation Z cohort.…”
Section: Underpinning Theoriesmentioning
confidence: 99%
“…, 2015). Food experiences are vital to visitors (Balıkçıoğlu Dedeoğlu et al ., 2022); accordingly, the food image of the destination is significant (Hsu et al ., 2018). With regards to our findings for hypothesis 9 and hypothesis 10, it was revealed that the “destination food image” significantly and positively influenced the “intention of tourist to visit/revisit” (β = 0.0.823, p < 0.001); however, negatively and insignificantly influenced the “intention of tourists to recommend” the food tourism destination (β = −0.0.085, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have found that travelers are increasingly drawn to trying to find new engrossment and interventions as a response to understanding the customs and gastronomic ethnicity of a specific area (Balıkçıo glu Dedeo glu et al, 2022). While examining travelers' local food experiences is indeed a new concept of academic research, prior studies (Chakraborty and Dash, 2023) suggest that consuming local food can impact travelers' LFC value, which may further influence their behaviors concerning the destination's food image and attitudes toward the local cuisine (Balıkçıo glu Dedeo glu et al, 2022). Therefore, as a factual representation of modern Indian culinary traditions, examining the impact of travelers' food consumption value on their subsequent behavior within the context of local Indian food remains critical and essential.…”
Section: Introductionmentioning
confidence: 99%
“…Yadav et al (2019) indicate no direct impact of subjective norms on green hotel choice, but their absence affects the decision. Conversely, Dedeoğlu et al (2022) applied TPB to conclude that subjective norms are insignificant in local food consumption intentions. Personal values are multidimensional and may be influenced by individual differences and situational factors.…”
Section: The Intention Behaviour Gap In the Sustainable Hospitality L...mentioning
confidence: 99%
“…Previous research in hospitality often used conventional human behaviour theories. It includes theory of planned behaviour (TPB) (Chatterjee and Barbhuiya, 2021; Chin et al , 2018; Dedeoğlu et al , 2022; Patwary et al , 2022; Teng et al , 2015; Yadav et al , 2019) and norm activation theory (Burhanudin and Unnithan, 2022; Han et al , 2016; Teng et al , 2023). These theories emphasise the influence of attitudes, values and beliefs on sustainable behaviour.…”
Section: Introductionmentioning
confidence: 99%